Analysis of Potential Skidway Loadout Failures Based on the Structural Strength and Foundation Settlement on the Fabrication Site in the Pre-Fabrication Phase. - Handayanu; Agus Juwarno; Yoyok Setyo Hadiwidodo (International Journal of Offshore and Coastal Engineering, 2025)
The abstract A fabrication company plans to undertake the construction of a topside structure with a weight exceeding 19,000 tons. Based on the Soil Investigation Report, it was found that the foundation in the fabrication area was previously used for the construction of a structure weighing 17,500 tons. Based on the consideration of the weight of the structure, it is necessary to review whether the fabrication area is capable of carrying out the construction of the topside structure until loadout. During the analysis process, it was found that the soil bearing capacity of the fabrication yard was 6108.99 MT at row support A1, while the minimum soil bearing capacity during the fabrication to loadout process at row support A1 was 6776.08 MT. Thus, it is necessary to modify the loadout area. In the process of assessing the strength of the soil foundation against structural loads, a support planning model is also made that will be used to support the topside structure during the fabrication process and also in carrying out loadout. The suitability of the structure and support will affect the process of assessing the strength of the soil foundation in parsing the potential for failure. In the process of analyzing the topside structure and support, under settlement conditions in the fabrication stage, it was found that there was a member that experienced a high enough stress with a UC value of 0.984 in member 2807-2808 on the deck leg above the row support. This occurred because during the settlement condition, there was a shift in the weight point of the structure with a joint reaction value of 4246.72 MT at the row support. During the analysis process on the bearing capacity of the foundation, topside structure, and support structure, the percentage of structural failure before modification of the loadout area is 2.12%, which is included in the failure category because it has a value above 1%.